Role of Media in Augmenting Violence in Adolescent Youth an Indian Perspective - John, Jimi; John, Sumy; T, Raghunadhan (Journal of New Media and Mass Communication, 2020)
Use of wide range of social media, particularly by adolescent youths, is on an increasing trend. Children who watch many hours of violence on television, while they were in school days tend to show higher levels of aggressive behavior when they became teenagers. Adolescent group normally watch and actively take part in various issues popping up in social media. More or less they spend considerable time on actively interacting with these social Medias. Among children, there is a natural tendency to imitate what they see. They are generally less sensitive to the pain and suffering of others. Often children turn to behave in aggressive manner. News on violence also contributes to increased violence, mainly in the form of imitative suicides and acts of aggression. Video games are clearly capable of producing an increase in aggression and violence. In nutshell, the paper attempt long-term longitudinal studies which may be capable of demonstrating long-term effects in Indian contest. Social media post on controversial remarks against any religion, community, deities, eminent personalities have greater repercussion. The study reveals that most of the adolescent youth have disturbed lifestyle. This has resulted in adverse changes in their behavioral pattern and are highly prone to the violence. The focus of the media should be to develop a conducive atmosphere in the society.